From Ritual to Entertainment: Transformations in Daruet AcehDance in Banda Aceh - Basri, Novysa; Alfi Syahrin; Aida Fitri; Novita Hidayani; Umul Aiman; Aris Munandar (Universitas Negeri Semarang, 2024)
The purpose of this study is to determine the social changes in the function of the Drop Daruet dance. This study uses a qualitative descriptive method, data collection techniques using the stages of observation, interviews and documentation with the aim of examining social changes in the function of the Drop Daruet Dance. This qualitative study can be used to understand social changes in the function of the Drop Daruet Dance. The results of this study indicate that the form of social change in the function of the Drop Daruet dance at the Cut Nyak Dhien Banda Aceh Studio, which was originally a medium of education and a medium of preaching, has changed into a medium of entertainment for dance performances only and the function of previous cultural values ​​has shifted as a meeting of young people but now it is only as a dance performance for entertainment. While the factors that cause social change in the function of the Drop Daruet dance at the Cut Nyak Dhien Banda Aceh Studio are the rapid development of technology in the current era of Globalization, the mindset of society that continues to develop and is critical, and changes in the tastes of the younger generation. Social changes in the function of the Drop Daruet dance, namely as a medium of education and a medium of preaching, have changed into a medium of entertainment and a medium of performance. This has both good and bad impacts on society.